Automated Quality Assurance of Online NIR Analysers. Issue 2 (1st June 2005) - Aaljoki, Kari
Abstract : Modern NIR analysers produce valuable data for closed-loop process control and optimisation practically in real time. Thus it is highly important to keep them in the best possible shape. Quality assurance (QA) of NIR analysers is an interesting and complex issue because it is not only the instrument and sample handling that has to be monitored. At the same time, validity of prediction models has to be assured. A system for fully automated QA of NIR analysers is described. The system takes care of collecting and organising spectra from various instruments, relevant laboratory, and process management system (PMS) data. Validation of spectra is based on simple diagnostics values derived from the spectra. Predictions are validated against laboratory (LIMS) or other online analyser results (collected from PMS). The system features automated alarming, reporting, trending, and charting functions for major key variables for easy visual inspection. Various textual and graphical reports are sent to maintenance people through email. The software was written with Borland Delphi 7 Enterprise. Oracle and PMS ODBC interfaces were used for accessing LIMS and PMS data using appropriate SQL queries. It will be shown that it is possible to take actions even before the quality of predictions is seriously affected, thus maximising the overall uptime of the instrument.